2013
DOI: 10.1007/978-1-4614-8560-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Using Animal Models of Celiac Disease to Understand the Role of MHC II

Abstract: Untreated CD patients develop increased numbers of intraepithelial lymphocytes, infl ammatory infi ltration of the lamina propria, intestinal permeability, and in a majority of cases, total or subtotal villous atrophy [ 1 ]. The trigger for the development of CD is gluten, typically derived from wheat, barley, and rye [ 2 ]. Gluten is a group of storage proteins found in wheat, rye, and barley. In wheat, gluten consists of two smaller subgroups of proteins, gliadins, and glutenins. In established CD patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…35,36 The poly(I:C)-based mouse model is one such system that has been used by several researchers for inducing signs and symptoms of celiac disease. 36 Poly(I:C) is a toll-like receptor-3 (TLR3) agonist that has shown to induce intestinal enteropathy similar to that observed in celiac disease. 37 In the first study that showed the effects of poly(I:C) on intestinal histopathology by Garside et al, 38 (CBAXBALB/c) F1 mice were injected intraperitoneally with poly (I:C), which resulted in a significant villous atrophy and crypt hyperplasia within 1 day post injection and recovery by 3 days post injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 The poly(I:C)-based mouse model is one such system that has been used by several researchers for inducing signs and symptoms of celiac disease. 36 Poly(I:C) is a toll-like receptor-3 (TLR3) agonist that has shown to induce intestinal enteropathy similar to that observed in celiac disease. 37 In the first study that showed the effects of poly(I:C) on intestinal histopathology by Garside et al, 38 (CBAXBALB/c) F1 mice were injected intraperitoneally with poly (I:C), which resulted in a significant villous atrophy and crypt hyperplasia within 1 day post injection and recovery by 3 days post injection.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of celiac disease models have been developed by researchers, which recapitulate different aspects of celiac disease. , The poly­(I:C)-based mouse model is one such system that has been used by several researchers for inducing signs and symptoms of celiac disease . Poly­(I:C) is a toll-like receptor-3 (TLR3) agonist that has shown to induce intestinal enteropathy similar to that observed in celiac disease .…”
Section: Discussionmentioning
confidence: 99%